Bifurcation analysis of the stability of one dynamical system with a follower force (Transport systems and technologies, 2019)
In this paper, for an inverted double pendulum with asymmetric follower force a mathematical model has been constructed in generalized coordinates. The dynamics of the system has been explored through both analytical and numerical approaches. Stability diagrams have been presented. The influence of the follower forces parameters on the dynamical behavior of the pendulum has been analyzed. Numerical simulation has been applied to obtain integral curves and phase portraits. The trajectories of the lower and upper poles of the pendulum have been constructed too.
Keywords: dynamical system, inverted double pendulum, follower force, stability